A new species of Chryxus Champion, with taxonomic notes on other species of the genus (Hemiptera, Heteroptera, Reduviidae, Chryxinae) - Gil-Santana, Hélcio R.; Leavengood, John M.; Bérenger, Jean-Michel; Martins, David Dos Santos; Oliveira, Jader [UNESP] (Pensoft Publishers, 2022)
Chryxus garcetebarretti sp. nov. from Paraguay is described, taxonomical notes on C. bahianus Gil-Santana, Costa & Marques, 2007 and C. tomentosus Champion, 1899 are provided; the latter species is recorded from French Guiana for the first time; a redescription of the genus Chryxus Champion, 1899 and an updated key for the genera and species of Chryxinae are presented.
Keywords: Assassin bugs; female and male genitalia; Guyana; Panama